Decision-making in critical circumstances among police officers - ŠALKAUSKAITĖ, ARŪNĖ; VALICKAS, GINTAUTAS; GRIKŠIENĖ, RAMUNĖ; RUKŠĖNAS, OSVALDAS (Kriminologijos studijos, 2015)
Decisions made by police officers may have dire consequences and determine their own or others’ lives. Therefore, this study was carried out with the aim to explore the characteristics of the decisions made by police officers in critical circumstances such as how decisions are made relating to the actual stress (cortisol level), personality characteristics, self-efficacy and stress coping strategies. The study involved 103 police officers from all over Lithuania, who participated in an occupational training in a Lithuanian police school. Critical circumstances were created by using simulator “PRISimTM”. Officers took part in the simulation of professional situations and completed decisionmaking tasks; their actions and decisions were evaluated by professional instructors, and mistakes made by officers were also recorded. Officers worked in pairs – in simulated situations, two officers performed the roles of “action” and “cover” officers. In addition, study participants have been compiling the NEO PI-R personality and stress coping questionnaires, the decision-making self-efficacy scale. A survey was also used to collect demographic data. The stress level was evaluated by measuring hormone cortisol level (saliva samples were taken from the officers before decision-making tasks and immediately after them). It was found that at the time of decision-making by police officers the stress (cortisol level) significantly increases. In addition, the results of the study revealed the following important points: a) decision-making in critical circumstances among police officers is associated with gender and with the position held (results indicated that male officers and officers holding the patrol duties made fewer mistakes in decision-making tasks than others); b) police officers most often use a problem-solving strategy to cope with stress, and rarely – emotional discharge; c) police officers’ self-efficacy related to decision-making in critical circumstances is higher than average. Self-efficacy is also associated with a lower number of mistakes made in decision-making tasks; d) neuroticism is associated with the evaluations scores of decision-making tasks (those police officers who got lower neuroticism scores, received better evaluations scores of decision-making tasks (according to all the used criteria)).
Keywords: police officers; decision-making; critical circumstances; cortisol